2021
DOI: 10.2174/1566524020666200712182137
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and Non-coding RNAs: New Insights into the Regulation of Breast Cancer

Abstract: : Breast cancer, a life-threatening serious disease with high incident rate among women, is responsible for thousands of cancer-associated death worldwide. Numerous investigations have been evaluated the possible mechanisms related to this malignancy. Among of them, non-coding RNAs (ncRNAs) i.e., microRNAs (miRNAs), long non-coding RNAs (lncRNAs), and circular RNAs have recently attracted attentions of researchers. In addition to recent studies for evaluating the role of ncRNAs in breast cancer etiology, some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 163 publications
0
11
0
Order By: Relevance
“…Evidence of the specific functional relationships between vitamin D/VDR and lncRNAs is summarized in Table 2 . Notably, the protective role of vitamin D against breast cancer through lncRNA-mediated pathways has been elucidated in detail [ 19 , 20 ]. Here we provided an update of current research and extracted the main regulatory axes with vitamin D/VDR and lncRNAs as reported there (Table 2 ).…”
Section: Functional Link Between Fat-soluble Vitamins (A D E and K) A...mentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence of the specific functional relationships between vitamin D/VDR and lncRNAs is summarized in Table 2 . Notably, the protective role of vitamin D against breast cancer through lncRNA-mediated pathways has been elucidated in detail [ 19 , 20 ]. Here we provided an update of current research and extracted the main regulatory axes with vitamin D/VDR and lncRNAs as reported there (Table 2 ).…”
Section: Functional Link Between Fat-soluble Vitamins (A D E and K) A...mentioning
confidence: 99%
“…We then tabulated and discussed the available research, highlighting any links between vitamins and lncRNAs. To our knowledge, this is the first review that has comprehensively profiled the co-contribution of lncRNAs and multiple vitamins to common pathways, beyond the vitamin D/VDR pathway that has been the focus of prior published studies [ 19 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, epigenetics can also be related to factors such as diet [ 123 ]. Other epigenetic modifications may also be related to vitamin D levels and the risk of developing BC, such as histone methylation [ 50 , 124 ] and the regulation and expression of miRNAs [ 125 , 126 , 127 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it seems that the genes coding transcription factors (TFs) are activated by 1,25(OH) 2 D 3 , which in turn regulates the expression of additional sets of genes [ 36 ], which could be described as secondary genomic response. Recently, regulatory effects of 1,25(OH) 2 D 3 on the expression of microRNAs and long noncoding RNAs have been uncovered as a potential anticancer mechanism [ 37 , 38 ].…”
Section: Vitamin D—overviewmentioning
confidence: 99%